Higher levels of free plasma mitochondrial DNA are associated with the onset of chronic GvHD. (October 2018) - Rozmus, Jacob; Ivison, Sabine; Kariminia, Amina; Leung, Vivian; Sung, Susanna; Subrt, Peter; Lee, Stephanie; Boilard, Eric; Walker, Irwin; Foley, Ronan; Lipton, Jeff; Gallagher, Geneviève; et al.
Abstract Toll-like receptor-9 (TLR9) responsive B cells have previously been associated with the onset of extensive chronic graft-versus-host disease (cGvHD). We hypothesized that the onset of cGvHD associated with a higher level of plasma-free mitochondrial DNA (mtDNA), a putative TLR9 agonist. Plasma cell-free mtDNA levels were measured in 39 adult patients post-HSCT with and without cGvHD. mtDNA was isolated from plasma and quantified by Q-PCR amplification. We correlated B cell responsiveness to CpG-DNA, a prototypical TLR9 agonist, and previously identified cGVHD biomarkers with mtDNA levels. Free plasma mtDNA were elevated in patients post-HSCT without cGvHD compared to normal non-HSCT adults. There was a significantly higher level of free plasma mtDNA associated with the onset of cGvHD (3080 ± 1586 versus 1834 ± 1435 copies/μL;p  = 0.02) compared to 6 months post-HSCT controls. Free mtDNA levels post-HSCT correlated with B cell responsiveness to CpG-DNA and known cGvHD biomarkers: CXCL10 (p  = 0.003), ICAM-1 (p  = 0.007), CXCL9 (p  = 0.03), sCD25 (p  = 0.05) and sBAFF (p  = 0.05), and percentage of CD21low B cells. Plasma levels of free mtDNA are increased in cGvHD and may represent an endogenous inflammatory stimulus for TLR9 expressing B cells.